An energy-based interpretation of sand liquefaction due to vertical ground motion - Tsaparli,V; Kontoe,S; Taborda,DMG; Potts,DM (Computers and Geotechnics, 2017)
In several recent earthquakes, high vertical ground accelerations accompanied by liquefaction were observed. Downhole records have also shown that large vertical accelerations do not necessarily originate from the source, but rather get amplified towards the ground surface. Given the advantages of energy-based interpretation of liquefaction triggering due to S-waves, this approach is used together with finite element analyses to investigate vertical motion amplification and ensuing liquefaction. The results show the importance of the post-resonance response cycles, while hysteretic damping based on total stresses, accounting for the water in the pores, is shown to be very low, explaining the observed amplification.